2015
DOI: 10.4028/www.scientific.net/amm.773-774.3
|View full text |Cite
|
Sign up to set email alerts
|

Melt Flow Index of Recycle ABS for Fused Deposition Modeling (FDM) Filament

Abstract: Abstract. This paper presents the melt flow index (MFI) of acrylonitrile butadiene styrene (ABS) and recycle ABS filament wire for Fused Deposition Modeling(FDM) machine. In this study, the effect of MFI on recycle ABS material was investigated experimentally based on the melting temperature, density, screw speed and material properties. The MFI result on ABS recycle in wire filament was investigated using Melt Indexer Machine(MIM). Based on the result obtained, it was found that, ABS recycle was increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The results of MVR measurements are summarised in Table 1, where the following behaviours can be observed: (1) while maintaining both the temperature and the test load constant, any increment in metallic load leads to smaller MVR values. This fact, also reported in [1113] indicates a viscosity rise. On the other hand, (2) for a given metallic load, the MVR value increases with the test temperature as well as with the test load, suggesting a pseudoplastic behaviour [8,9].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The results of MVR measurements are summarised in Table 1, where the following behaviours can be observed: (1) while maintaining both the temperature and the test load constant, any increment in metallic load leads to smaller MVR values. This fact, also reported in [1113] indicates a viscosity rise. On the other hand, (2) for a given metallic load, the MVR value increases with the test temperature as well as with the test load, suggesting a pseudoplastic behaviour [8,9].…”
Section: Resultssupporting
confidence: 82%
“…Elaborated feedstocks were evaluated via MFI measurements performed in a laboratory melt flow indexer (Dynisco LMI 5000) under 2 and 5 kg loads at 150°C and 170°C as an additional means of evaluating whether their flow was appropriate for injection moulding. MFI measurements were also useful for Sa'ude et al [11] in determining proper metallic loading. Moreover, Thavanayagam et al [12,13] found that the results of the MFI tests had the same trend as the fluidity test performed by capillary rheometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the point of view of the material, the acrylonitrile-butadiene-styrene copolymer (ABS) is known for its excellent mechanical and impact strengths, dimensional stability, good chemical resistance, low water absorption and high filling capacity, arising as a popular thermoplastic material of choice for FDM applications as it offers satisfactory processability and a relatively low melting temperature [5,[26][27][28][29]. The manufacturing of ABS composites through additive manufacturing (AM) techniques, such as FDM, has been demonstrated [30][31][32][33][34], and melt flow index (MFI) analysis has been a popular testing choice to evaluate the flow behaviour trends of ABS composites developed for 3D printing [35][36][37][38][39][40][41]. Isa et al (2015) [35] and Sa'ude et al (2016) [36] studied the behaviour of ABS/copper composites, and Kumar et al (2019) [38] carried out similar work on ABS/aluminium composites, with all of them targeting the development of materials for extrusion-based AM processes; nonetheless, their results indicated that the filler has distinct effects on MFI depending on its content, suggesting that there would be no direct dependence between the loading content and MFI.…”
Section: Introductionmentioning
confidence: 99%
“…Polylactic acid (PLA) is a lactic acid-based polymer composed of renewable resources that have a greater impact area than petroleum-based plastics [2]. Acrylonitrile butadiene-styrene (ABS) material is one of the polymers used in rapid prototyping technology, which is widely preferred in FDM that was developed by Stratasys Inc. [3][4]. The gain in pre-selection of ABS and PLA filaments emerged after exchanging ideas with 3D printer suppliers [5].…”
Section: Introductionmentioning
confidence: 99%